2010
DOI: 10.1021/ja102673m
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Single-Strand DNA: Single-Walled Carbon Nanotube Hybrids by Watson−Crick Base-Pairing

Abstract: It has been known that single-strand DNA wraps around a single-walled carbon nanotube (SWNT) by pi-stacking. In this paper it is demonstrated that such DNA is dissociated from the SWNT by Watson-Crick base-pairing with a complementary sequence. Measurement of field effect transistor characteristics indicates a shift of the electrical properties as a result of this "unwrapping" event. We further confirm the suggested process through Raman spectroscopy and gel electrophoresis. Experimental results are verified i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…These observations can be reconciled with the observations of Jung et al, 28 who suggested that the energy released by a 17 bp duplex formation is enough to facilitate desorption of the dsDNA. The values estimated by the authors predict that the 24 bp dsDNA used in our simulation would have a desorption energy of around 56 kcal/mol, which is 2 orders of magnitude larger than thermal fluctuation at ambient conditions.…”
Section: ■ Resultssupporting
confidence: 72%
“…These observations can be reconciled with the observations of Jung et al, 28 who suggested that the energy released by a 17 bp duplex formation is enough to facilitate desorption of the dsDNA. The values estimated by the authors predict that the 24 bp dsDNA used in our simulation would have a desorption energy of around 56 kcal/mol, which is 2 orders of magnitude larger than thermal fluctuation at ambient conditions.…”
Section: ■ Resultssupporting
confidence: 72%
“…As one of the most powerful building blocks for self‐assembled nanostructures,10 DNA has the potential to play a major role in any such development. Although the selective dispersion of SWNTs with pristine DNA was realized,11 the subsequent controlled assembly through hybridization with complementary DNA (cDNA) is unfeasible because of the unwrapping of DNA attached to the tube 12. Other studies that combine DNA and SWNTs have entailed covalent bond formation between the two moieties13 or the chemical modification of DNA wrapped around the nanotubes 14.…”
mentioning
confidence: 99%
“…Karachevtsev et al prepared DNA-SWNT hybrids with polynuclueotides and studied aggregate formation of the hybrids [38,39]. Jung et al also demonstrated detachment of DNA molecules from SWNT surfaces through DNA hybridization [40]. Jeng et al estimated the kinetic parameters of DNA hybridization on SWNT surfaces [41].…”
Section: Introductionmentioning
confidence: 99%